High tensile-strength and ductile titanium matrix composites strengthened by TiB nanowires - Huang, Liqing; Wang, Lihua; Qian, Ma; Zou, Jin (Scripta materialia, 2017)
A three-dimensional network-woven architecture made of TiB nanowires has been designed and realized in the matrix of a Ti6Al4V alloy. The architecturally nanostructured design was achieved by dispersing nanoparticles of B4C or B onto the surfaces of spherical Ti6Al4V powder particles via mechanical mixing and subsequent consolidation by spark plasma sintering. The as-sintered nanostructured Ti6Al4V-TiB composites demonstrated excellent tensile strengths and ductility that are required for critical applications. The in situ formed TiB nanowires with aspect ratios up to 300 contributed to the high tensile strengths while the architectural design of the TiB nanowires ensured the good tensile ductility. [Display omitted]